Monetary Policy Under Imperfect Capital Markets in a Small Open Economy - Tuladhar, Anita (American Economic Review, 2003)
Following the financial crises of the late 1990's an increasing number of emergingmarket countries have adopted a flexible exchange-rate regime and an inflation-targeting monetary-policy framework. This trend has generated a growing debate on the appropriate monetary-policy rule for "financially fragile" economies with thin and incomplete financial markets that are subject to highly volatile capital flows. Within this context, I examine the implications of alternative monetary-policy rules and the choice of instruments and targets in a small open economy with imperfect capital markets. I compare a benchmark efficient-markets model with a monetary-targeting regime and three different inflation-targeting rules: the Taylor rule, a CPI inflation-target rule, and a non-tradable inflation-target rule. Furthermore, I study how sensitive the results are to varying degrees of capital-market integration. In addressing this question of the "second best" policy, the paper resembles that of Michael Devereaux and Phillip Lane (2001), who study the role of financial accelerator effects on various monetary-policy rules. I adopt a small open-economy setup rather than a two-country framework. In contrast to most small open-economy models, however, this paper does not assume a zero current-account balance. Net foreign-asset holdings and capital flows affect real volatility through the interest-rate risk premium. Given the significant role the risk premium plays in the external borrowing costs for emerging markets, this channel may have important consequences for economic dynamics.